Dual computer displays reduce extraneous cognitive load. - Miller, Robert A.; Stenmark, Cheryl K.; Ittersum, Kyle van (Journal of Computer Assisted Learning, 2020)
Dual display desktop computers are becoming more prevalent in the home, workplace, and schools, yet there has been little research into how learning and productivity are impacted by having a second display. One useful method in exploring this question is to measure cognitive load during an intensive learning event. This study compared perceived cognitive load among participants in a military training program using one or two computer displays. Participants using dual monitors reported lower unnecessary cognitive load than participants using one monitor. The implications of these findings for theory and practice are discussed. Lay Description: What is already known about this topic: Our minds have access to limited cognitive bandwidth when learning new material.The difficulty of the material combined with the learners' previous experience impact how much cognitive load is induced while learning.Cognitive load requirements that exceed the learner's ability can hinder retention.Curriculum developers design lessons to maximize learning and reduce unnecessary cognitive load. What this paper adds: Using a second computer screen on a learner's desktop can reduce extraneous cognitive load by up to 20%.Reducing unnecessary cognitive load increases available bandwidth for learning and increases retention. Implications for practice and/or policy: Adding a second screen to learners' workstations can allow learners to process complex material more easily.Companies and universities can justify costs of additional equipment by increased potential for productivity.